An uncovered extensive fusion of two separated periapical lesions in CBCT imaging: the importance of multiplanar radiographic appraisal - Aga Satria Nurrachman; Norlaila Sarifah; Eha Renwi Astuti (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: This report is aimed to present a case of an uncovered fusion of two seemingly separated periapical rarefying osteitis lesions on two adjacent teeth through Cone Beam Computed Tomography (CBCT) imaging and to describe the significance of a comprehensive multiplanar appraisal in interpreting CBCT radiographs. Case Report: An 18-year-old female patient came to Universitas Airlangga Dental Hospital for a CBCT examination of her right central maxillary incisor (tooth 11) as referred by her dentist. Based on the clinical report provided, the patient had a slight palpable swelling of the labial gingival anterior maxilla with sign of crepitus. Caries lesions were found on teeth 11 and 12 in which the vitality tests showed negative responses. Thus, it was provisionally suspected as a periapical inflammatory lesion. CBCT was done and the 3D-reconstructed images of the bone showed there were two neighboring radiolucent ovoid lesions attached on one-third apical of teeth 11 and 12, separated by a firm-apparent cortex. It was later discovered that the two lesions were actually fused as one elongated and extensive lesion through the multiplanar appraisal of three orthogonal views provided in CBCT application. Conclusion: CBCT 3D-reconstructed and panoramic reformatted images should be used with caution, either for linear measurement or diagnostic purposes, as they should only be used to illustrate the diagnosis and/or provide a better understanding of the problem to the patients and their treatment plans. A comprehensive multiplanar appraisal is required to provide a diagnostically complete interpretation.